Thunder and shadow - Hunter, Erin (Hunter, Erin. Warriors, a vision of shadows, 2016)
After Alderpaw returns from the gorge that was once home to SkyClan, the ferocious cats who drove SkyClan out trace Alderpaw's path back to ShadowClan, making it their next target.